Interfaz entre bioética y relaciones internacionales - Manchola Castillo, Camilo Hernán (2016)
Recently, bioethics and international relations have gotten closer to one another, probably as a result of the motivation of bioethics to intervene in global affairs. However, this relationship has only been on the practical level. This study’s objective, through a literature review, is to highlight the huge potential that the epistemologies of both areas have to build a more fruitful dialogue. 18 articles relating both areas were retrieved from databases Scopus, Web of Science, Bireme and PubMed. The articles were then grouped in three categories of analysis: bioethics and global health; international organizations and bioethics; and international relations and bioethics. This study concludes that an epistemological approaching between these areas is desirable and proposes the establishment of two new areas of study: international relations in health and international relations from the South, drawing upon the conceptual basis developed by Latin-American bioethics.